Parental and peer social support is associated with healthier physical activity behaviors in adolescents: a cross-sectional analysis of Texas School Physical Activity and Nutrition (TX SPAN) data - Amier Haidar; Nalini Ranjit; Natalie Archer; Deanna M. Hoelscher (BMC, 2019)
Abstract Background Parental and peer support can influence children's physical activity; however, these associations have not been fully examined in a multi-ethnic population across early and late adolescence. The objective of this study was to examine associations between perceived parental/peer social support, perceived parental disapproval for not exercising, and physical activity/screen time behaviors among a multi-ethnic sample of adolescents. Methods The Texas School Physical Activity and Nutrition (TX SPAN) survey is a cross-sectional statewide probability-based survey, used to assess obesity-related behaviors such as diet and physical activity. The SPAN 2009-2011 study measured 8th and 11th grade students using a self-report questionnaire with established psychometric properties, along with objectively measured height and weight. Associations were examined using multiple logistic and linear regression. Results For every 1-point increase in parental physical activity support, adolescents had 1.14 higher odds of engaging in five or more days of moderate physical activity per week (p < 0.001), and 1.12 higher odds of engaging in three or more days of vigorous physical activity per week (p < 0.001). For every 1-point increase in peer physical activity support, adolescents had 1.17 higher odds of engaging in five or more days of moderate physical activity per week (p < 0.001), and 1.15 higher odds of engaging in three or more days of vigorous physical activity per week (p < 0.001). Conclusions Parental and peer social support is associated with positive physical activity behaviors in adolescents. Strategies to focus on parent and peer support should be integral to intervention programs designed to increase physical activity in adolescents in middle and high schools.